2000
DOI: 10.1007/s101470050104
|View full text |Cite
|
Sign up to set email alerts
|

Lung adenosquamous carcinoma with lingual and cardiac metastases

Abstract: Metastatic lingual tumors are very rare, and hematogenous myocardial metastasis is also relatively uncommon. We report a case of lung adenosquamous carcinoma with metastases to the tongue and the myocardium. A 65-year-old man underwent a partial upper lobectomy for a primary lung cancer in June 1997. He developed a local recurrence and received two courses of radiotherapy, in March and September 1998. A follow-up computed tomography (CT) scan showed a myocardial tumor, suggestive of cardiac metastasis. In Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Several studies have recommended palliative treatment (e.g., surgical treatment, chemotherapy, and radiotherapy) to improve the quality of life (QOL) and to maintain the patient's comfort 7,8 . We found 54 cases of oral metastasis of PCs that were reported from 1991 to 2021 in PubMed and Google scholar 9–45 and reviewed these cases, including our case. Kaplan‐Meier survival analyses were performed to determine whether palliative treatment affected overall survival.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several studies have recommended palliative treatment (e.g., surgical treatment, chemotherapy, and radiotherapy) to improve the quality of life (QOL) and to maintain the patient's comfort 7,8 . We found 54 cases of oral metastasis of PCs that were reported from 1991 to 2021 in PubMed and Google scholar 9–45 and reviewed these cases, including our case. Kaplan‐Meier survival analyses were performed to determine whether palliative treatment affected overall survival.…”
Section: Discussionmentioning
confidence: 91%
“…In our review, 41 of 54 patients received palliative treatments, and surgical treatments were common ( n = 10), followed by chemoradiotherapy ( n = 8) (Table 1). 8–44 There were no significant differences in the survival times between patients with and without palliative treatment at 6.49 and 4.36 months, according to the results of the Kaplan‐Meier test (log rank test: P = 0.437, Figure 4), which suggested that palliative treatment had no effect on survival time. Our patient was able to consume food orally using the upper denture after surgical treatment, showing that even if radical therapy cannot be administered, palliative treatment for maintaining oral function may contribute to the improvement of the QOL.…”
Section: Discussionmentioning
confidence: 95%